An alkali-tolerant strain Microbacterium esteraromaticum C26 produces a high yield of cation-independent bioflocculant - Cong Liu; Rongnan He; Weijie Liu (AIMS Environmental Science, 2016)
A novel cation-independent bioflocculant BF-C26 produced by an alkali-tolerant strain Microbacterium esteraromaticum C26 was investigated in this study. The fermentation conditions for BF-C26 production were analyzed, including initial pH, carbon source, nitrogen source and the ratio of carbon source to nitrogen source. The result showed that 4.92 g/L bioflocculant BF-C26 was obtained at the following optimized conditions: 3 g/L glucose as carbon source, 10 g/L peptone as nitrogen source and initial pH 8.1. The component assay showed that BF-C26 was a complex of 52.8% proteins and 28.1% polysaccharides. The effects of physicochemical parameters including metal ions, temperature, pH and bioflocculant dosage on flocculating properties of BF-C26 were optimized. The highest flocculating rate of 94.82% was achieved when 4 mg/L BF-C26 was added into the kaolin suspension at pH 8.23 and 30 °C. In this study, Microbacterium esteraromaticum was reported for the first time as a cation-independent bioflocculant producing strain.